Thin film organic thermoelectric generator based on tetrathiotetracene - Pudzs, Kaspars; Vembris, Aivars; Rutkis, Martins; Woodward, Simon (Wiley-VCH Verlag, 2017)
Thin films of p- and n- type organic semiconductors for thermo-electrical (TE) applications are produced by doping of tetrathiotetracene (TTT). To obtain p-type material TTT is doped with iodine during vacuum deposition of thin films or by post-deposition doping using controlled exposure to iodine vapors. Thermal co-deposition in vacuum of TTT and TCNQ is used to prepare n-type thin films. The attained thin films are characterized by measurements of Seebeck coefficient and electrical conductivity. Seebeck coefficient and conductivity could be varied by altering the doping level. P-type TTT:iodide thin films with a power factor of 0.52 μWm-1K-2, electrical conductivity of 130 S m-1 and Seebeck coefficient of 63 μV K-1 and n-type TCNQ:TTT films with power factor of 0.33 μWm-1K-2, electrical conductivity of 57 S m-1 and Seebeck coefficient of -75 μV K-1 are produced. Engineered deposition of both p- and n-type thermoelectric conducting elements on the same substrate is demonstrated. A proof of concept prototype of planar thin film TE generator based on a single p-n couple from the organic materials is built and its power generation characterized.
This is the peer reviewed version of the following article: K. Pudzs, A. Vembris, M. Rutkis, S. Woodward, Adv. Electron. Mater. 2017, 1600429, which has been published in final form at http://onlinelibrary.wi...002/aelm.201600429/full This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Self-Archiving.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Thermoelectrics; Thin Films; Organic Electronics; Doping